PERANAN KEGIATAN KAJI TERAP TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP PENYULUH PERTANIAN DALAM TEKNOLOGI PENGELOLAAN TANAMAN TERPADU CABAI - Eko Nugroho Jati; Jemmy Rinaldi; I Nyoman Adijaya (Universitas Udayana, 2019)
In the process of disseminating technological innovation, there is still an information gap between providers of technological innovation, namely the Agricultural Research Agency and regional agricultural stakeholders and farmers. Agricultural Research and Development Agency has produced many agricultural technological innovations, one of which is technological innovation to overcome obstacles in the cultivation of chili is the Integrated Crop Management (PTT) Chili technology. One way to overcome the problem of inaction in the application of technological innovations produced is one of them is an applied review activity targeting Agricultural Extension Workers in the regions. This study aims to: determine the increase in knowledge and attitudes of Agricultural Instructors in PTT Cabai Rawit technology through applied study activities. The study was conducted at the Agricultural Extension Center (BPP) of Banjarangkan District, Klungkung Regency with a survey method of 20 agricultural extension respondents using a questionnaire. Data were analyzed descriptively quantitatively. The results of the study show that: Applied Study Activities have an impact on changes in knowledge and attitudes of agricultural instructors in PTT Chili technology, namely the knowledge of Agricultural Instructors has changed from an average score of 2.04 (medium knowledge) to an average score of 2.89 (high knowledge) and attitudes of farmers from an average score of 2.31 (doubtful attitude) to an average score of 2.81 (agreeing attitude).